A new Antarctic species of Aristias Boeck (Crustacea, Amphipoda, Aristiidae), with remarks on the genus in Antarctica - Kilgallen, Niamh M. (Zootaxa, 2010)
A new species of aristiid, Aristias excavatus sp. nov., is described from an Antarctic sponge. The systematics of the genus is discussed. There are now 28 known species in the genus Aristias, with just three recorded from Antarctic waters. The actual number of Antarctic species is likely to be higher, however, because many of these records were probably incorrectly attributed to A. antarcticus.